Implementation of Extracurricular Traditional Gamelan Music in the Development of Creativity of Group B Children at Kindergarten Negeri Pembina Kota Semarang - Isnaini Nurkhasanah (BELIA Early Childhood Education Papers, 2026)
The purpose of this study is to describe the implementation of gamelan extracurricular activities in developing children's creativity and the factors that support or inhibit children's creativity. This study uses a qualitative descriptive research method. The data collection technique consists of observation, interviews, and documentation. The primary data collected by the researcher was obtained directly from gamelan extracurricular teachers, group B class teachers, and school principals. Data validity techniques use source triangulation and techniques. Data analysis techniques consist of data collection techniques, data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of gamelan extracurricular activities goes through the planning stage by determining the schedule, the implementation process through the initial, core, and closing activities, and the evaluation is carried out directly after the activity ends. The implementation of gamelan extracurricular activities can develop creative attitudes in children, namely having curiosity, availability to answer questions, openness, courage in taking risks, and confidence. In addition, children also have a sense of sensitivity to sound, rhythmic tone, love harmony, and beauty. The supporting factor for the development of creativity through this program is the availability of supporting facilities and infrastructure. The inhibiting factors are the child's ability, interest, and condition.